Australian citizenship in interesting times. (5th May 2015) - Mark Vicars and Dr Jon Austin, Dr; Cary, Lisa; Pruyn, Marc; Austin, Jon
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to understand, more deeply, what the field of citizenship education stands for, in both theory and practice, historically and currently, and especially, in relation to the new Australian Curriculum: Civics and Citizenship. The authors have drawn on the backgrounds in social studies/social education, multicultural education, democracy education and Indigenous studies, in order to more deeply and profoundly understand "civics and citizenship education" and what it represents today in Australia. Design/methodology/approach – Methodologically, the authors see epistemological spaces as discursive productions from post-structural/post-modern and critical perspectives. These positions draw upon the notion of discourse as an absent power that can validate/legitimize vs negate/de-legitimize. The authors employ a meta-level analysis that historicizes the spaces made possible/impossible for those in deviant subject positions through a critique of the current literature juxtaposed with a presentation and analysis of "citizenship snapshots" of the authors. In this way, the authors attempt to move beyond conceptions of deviant citizenship based on curricular content and instructional method, and explore the realms of epistemology through the study of exclusion/inclusion. Findings – Reflecting the highly personal and individualized nature of the type of research required to be conducted in this aspect of national and personal identity, each of the authors draws here on personal experiences with aspects of citizenship that are not noticeably present in the current national curriculum. Specifically, the three "citizenship snapshots" at the heart of this paper's discussion and analysis – snapshots constructed by academics who both understand and resist the racialised/classed privilege bestowed upon them by nation states – are: "The boomerang citizen", "privileged and non-privileged citizen immigrants", and "Indigenous citizenship, sovereignty & colonialism". Originality/value – Drawing both on the current international scholarship on citizenship, power and social changes and the critical/post-structuralist qualitative methodology set forth by the authors, this work describes and problematizes the evolving "citizenship identities" in an attempt to critically assess the new civics and citizenship component of the Australian curriculum; understand the ongoing development of national, regional and global "trans/international" citizenship youth identities; and make connections between citizenship education, identity development and the global youth "occupy"/liberation movements.